One-pot synthesis of 2,4,6-triarylpyridines by cyclocondensation between aryl aldehyde, acetophenone derivative, and ammonium acetate using Al/Ag3PO4 as a new and green bimetallic catalyst - El Hallaoui, Achraf; Merroun, Youssef; Chehab, Soukaina; Ghailane, Rachida; Souizi, Abdelaziz (Monatshefte für Chemie, 2023)
The 2,4,6-trisubstituted pyridines constitute an important family of heterocyclic compounds widely used in industry, especially in pharmaceuticals, making their preparation a crucial challenge for organic chemists. In continuation of our approach in the preparation and development of new catalytic systems, we present in this paper a highly efficient one-step synthesis of triarylpyridine by Al/Ag 3 PO 4 phosphate bimetallic catalysis from the condensation of acetophenone derivatives, aryl aldehydes, and ammonium acetate under mild and environmentally friendly conditions. This methodology offers several advantages: excellent yields and shorter reaction times. In addition, the catalyst exhibited remarkable reusable activity. Compared to previous methods, our procedure allows a very flexible, more straightforward, faster, and more efficient preparation of substituted pyridines. Graphical abstract